Strengthening teacher competence for leading and sustaining the implementation of the Merdeka Curriculum - Erna Kusumawati; Khoerul Umam (Cogent Education)
The Merdeka Curriculum, implemented over the past three years, has highlighted a dynamic shift, impacting both teachers and students. This study employs a phenomenological qualitative approach, based on Miles and Huberman’s framework, to evaluate the impact of the Merdeka Curriculum on teacher competence in Indonesia. The research involved teachers and educational stakeholders, particularly in public schools. Data were collected through participant observation, in-depth interviews, and documentation studies across 56 public high schools affiliated with the first wave of driving schools. The study applied Interpretative Phenomenological Analysis (IPA) and NVivo software to explore how participants interpret their personal and social realities. The findings provide a comprehensive understanding of the Merdeka Curriculum’s impact on teacher competence, especially in fostering 21st-century professionalism in teaching. This research offers valuable insights for evaluating educational policies, with the primary output being a policy brief for the Indonesian government.